Faktor Determinan Kejadian Stunting Pada Balita Usia 12-24 Bulan Di Wilayah Kerjah Puskesmas Oesapa Kota Kupang - chindy detakiuk; Yohanes Don Bosko Demu Demu; Albert Matu Salak Baumali (Poltekkes Kemenkes Kupang, 2026)
Stunting remains a prominent nutritional issue in Indonesia, including in the city of Kupang, where the prevalence reaches 31.9%. Identifying local risk factors is crucial for determining appropriate intervention strategies. This study aims to analyze the relationship between direct breastfeeding, a history of low birth weight (LBW), maternal knowledge level, and family income with the incidence of stunting in toddlers aged 52–104 weeks. This study employed a cross-sectional design. A sample of 76 toddlers was selected from a population of 301 toddlers in the service area of the Oesapa Community Health Center, Kupang City. Data analysis showed no significant association between stunting and direct breastfeeding (p=0.204), a history of LBW (p=0.204), maternal knowledge level (p=0.824), or parental income (p=0.699). These findings indicate that these factors are not the sole determinants in this region, and there is a possibility of influence from other external factors not examined in this study, such as environmental sanitation, access to clean water, or the frequency of infections among toddlers. The internal and socioeconomic factors tested were not found to have a direct effect on stunting at the Oesapa Community Health Center. A more comprehensive approach is needed through nutrition education, improved child-rearing practices, interventions targeting environmental factors, and the strengthening of cross-sectoral health services.